Identification of a new repetitive element in the sex chromosomes of Leporinus elongatus (Teleostei : Characiformes : Anostomidae): new insights into the sex chromosomes of Leporinus - Parise-Maltempi, P. P.; Martins, C.; Oliveira, C.; Foresti, F. (Karger, 2007)
Leporinus elongatus represents an interesting model for studies on chromosome evolution since it possesses a conspicuous ZZ/ZW sex chromosome system that has been characterized mainly by basic cytogenetic techniques. In the present study we describe a dispersed repetitive element ( named Le SpeI) related to the sex chromosomes of L. elongatus. Females revealed clusters of Le SpeI on the long arm of the W chromosome and in the acrocentric NOR-bearing chromosome pair. In males, the signal was restricted to the pericentromeric region of the NOR-bearing chromosomes. Considering the results obtained in the present study using FISH, NOR and C-banding, together with findings from previous studies, it can be inferred that the sex chromosome system of L. elongatus is still undergoing an evolutionary process. The data suggest novelties in relation to the sex chromosomes of the genus Leporinus with the description of a multiple sex chromosome system involving the NOR-bearing chromosomes. Therefore, it is hypothesized that the simple ZW chromosome system previously described for L. elongatus rather is a multiple Z(1)Z(1)Z(2)Z(2)/Z(1)W(1)Z(2)W(2) system. Copyright (c) 2007 S. Karger AG, Basel